Biopsychosocial and Economic Determinants of Low Birth Weight in Jambi, South Sumatera: Path Analysis - Trisnawati, Iga; Salimo, Harsono; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Low birth weight (LBW) is one of the main risk factors of neonatal mortality and morbidity. It is an important public health issue particularly in developing countries. Worldwide, LBW shares around 15-20% of birth outcome. In Indonesia, LBW shares about 10.2% of birth outcome. In theory, the risk factors of LBW include not only biological aspect but also psychosocial and economic aspects. This study sought to estimate the biopsychosocial and economic determinants of LBW in Jambi, South Sumatera, using path analysis approach. Subjects and Method: This was an analytic observational study with case-control design. The study was carried out at 20 community health centers in Jambi, South Sumatera, from December 2017 to January 2018. A total sample of 200 newborn infants consisting of 50 LBW and 150 normal birth weight newborn infants were selected for this study by fixed disease sampling. The dependent variable was birth weight. The independent variables were gestational age, infant sex, maternal mid-upper arm circumference (MUAC), maternal gestational stress, maternal education, family income at gestational period, and sanitation. Data on birth weight and MUAC were taken from obstetric record. The other data were collected by questionnaire. The data were analyzed by path analysis. Results: The risk of LBW directly decreased with gestational age ?37 weeks (b= -5.06; 95% CI= -6.49 to -3.62; p<0.001), male sex (b= -0.99; 95% CI= -2.12 to -0.12; p= 0.081), low maternal stress (b= -2.35; 95% CI= 14.01 to -0.70; p= 0.005), and good sanitation (b= -1.04; 95% CI= -2.13 to -0.05; p= 0.062). Gestational age increased with family income (b= 1.74; 95% CI= 0.96 to 2.52; p<0.001). Low maternal stress was positively affected by high family income (b= 1.34; 95% CI= 0.197 to 2.50; p= 0.022). Good sanitation was positively affected by high family income (b= 0.71; 95% CI= 0.01 to 1.41; p= 0.046). High family income was positively affected by high education level (b= 1.37; 95% CI= 0.57 to 2.18; p= 0.001) Conclusion: The risk of LBW directly decreases with gestational age ?37 weeks, male sex, low maternal stress, and good sanitation. LBW is indirectly affected by maternal education and family income. Keywords: biopsychosocial, economic, determinant, LBW Correspondence: